THE EFFECT OF ECONOMIC GROWTH AND INFLATION ON FOREIGN DIRECT INVESTMENT (FDI) IN ASEAN COUNTRIES - Muttaqien; Wardhiah; Muhammad Hafizh; Frengki Putra Ramansyah; Cut Zira Maulida (PT. Radja Intercontinental Publishing, 2024)
This study aims to determine and see the effect of economic growth and inflation on foreign direct investment (FDI), besides that this study is also to analyze economic growth and inflation on FDI in ASEAN countries. The population in this study were 11 ASEAN countries but after researchers determined the criteria, researchers only took 7 samples in this study. This study uses panel data regression data analysis. The results showed that the economic growth variable had a positive and significant effect while inflation had no effect on FDI. While simultaneously economic growth and inflation affect foreign direct investment (FDI).